Innovation networks and social enterprises. A social network analysis on Italian social enterprises - Metallo, Gerardino; Cuomo, Maria Teresa Maria; Tortora, Debora; Galvin, Maureen (Piccola Impresa / Small Business, 2016)
In recent years both studies and corporate practice highlight the relevance of innovation networking enabling for profit and social enterprises to create knowledge, skills and technology sharing systems for innovation. Paying attention to the for-benefit economy, the aim of the research is to verify whether in social enterprises relational attitudes and cooperation influence the propensity for innovation, from an “innovation network” perspective. By means of a Social Network Analysis, combined with an Organizational Network Analysis and a Sentiment Analysis the survey is based on a sample of 200 italian social enterprises, out of 910 members of a really relevant non-profit Association in Italy. Preliminary findings show an emerging model, termed in fieri centric innovation network, in which the diffusion of knowledge throughout the network − crucial in order to create innovation − has to constitute a priority in its development policies.